A Study on Teachers Perception about Components of English Handwriting in Pakistan - Hafiz Tahir Jameel,Farhan Sarwar, Beverly H. Moskowitz, (PJE, 2023)
Handwriting is an essential element of school activities for the schoolaged children. Good or legible handwriting remains a constant task for the teachers and students throughout the whole day. Teachers recognize legible handwriting at a glance due to their routine work in the schools. Which criterion led to a teacher’s determination of good handwriting was the purpose and research question posed in this study.